Methods To Determine Pillar Stress Distribution And Its Effect On Stability - David P. Conover (International Conference on Ground Control in Mining, 1989)
The effects of stress distribution on pillar stability were evaluated through rock mechanics studies conducted in three underground room-and-pillar coal mines. Results of the three field instrumentation programs are presented to illustrate the use of borehole pressure cells to determine vertical stress distribution in coal pillars at various stages of mine development. Vertical stresses and stress changes are determined using methods developed at the Bureau of Mines. Measured stress distributions are compared against theoretical distributions and possible explanations for observed behavior are discussed. Results indicate that stresses and stress changes calculated from pressure cell data are inconsistent with theoretical values; however, the data are useful for qualitative evaluation of trends over time. Calculated values are found to be sensitive to coal properties and initial setting pressures of the cells.